2016
DOI: 10.1038/srep21786
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Properties of Monolayer and Bilayer MoS2 Contacts with Metals: Beyond the Energy Band Calculations

Abstract: Although many prototype devices based on two-dimensional (2D) MoS2 have been fabricated and wafer scale growth of 2D MoS2 has been realized, the fundamental nature of 2D MoS2-metal contacts has not been well understood yet. We provide a comprehensive ab initio study of the interfacial properties of a series of monolayer (ML) and bilayer (BL) MoS2-metal contacts (metal = Sc, Ti, Ag, Pt, Ni, and Au). A comparison between the calculated and observed Schottky barrier heights (SBHs) suggests that many-electron effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
239
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(284 citation statements)
references
References 71 publications
41
239
2
Order By: Relevance
“…The resulting cohesive energy is found to be ß0.34 eV per interface atom which is higher than what is typically expected for weak physisorption interactions (Desjonquères & Spanjaard, 1996). This value is however consistent with other modelling works on 2D heterostacks (Zhong et al, 2016) and points towards the presence of a strong interaction at the interface between the two phases (Lefebvre et al, 1998), which leads to a distortion in the atomic structure of the β-SnS layer, leading to the formation of the new β' phase.…”
Section: Fig 6 Evolution Of the Interaction Energy Per Surface Atommentioning
confidence: 45%
“…The resulting cohesive energy is found to be ß0.34 eV per interface atom which is higher than what is typically expected for weak physisorption interactions (Desjonquères & Spanjaard, 1996). This value is however consistent with other modelling works on 2D heterostacks (Zhong et al, 2016) and points towards the presence of a strong interaction at the interface between the two phases (Lefebvre et al, 1998), which leads to a distortion in the atomic structure of the β-SnS layer, leading to the formation of the new β' phase.…”
Section: Fig 6 Evolution Of the Interaction Energy Per Surface Atommentioning
confidence: 45%
“…Recent experimental 20,61 and theoretical studies 60,62,63 have found a similar discrepancy. According to these studies, the Fermi level is partly pinned as a result of two interface effects: first, due to a metal work function modification resulting from a dipole formation at the interface, and second, by the introduction of gap states due to the weaker Mo–S bonding induced by interface metal–S interactions at the interface.…”
Section: Results and Discussionmentioning
confidence: 73%
“…The bright borders suggest the presence of an enhanced conductivity at the edge, an effect predicted by Density Functional Theory (DFT) calculations. [54] We observe that MoS 2 has a strong conductance anisotropy: the conductivity between two adjacent van der Waals (vdW) bonded S-Mo-S sheets is extremely low with a resistivity that has been measured to be 2200 times larger through the basal planes as compared to that measured along Mo planes. [55] This behavior means that the single layer nanoplatelets are an optimal structure compared to a multilayer crystal because electrons only need to be transferred from the contact to the platelets.…”
Section: Transport Measurementsmentioning
confidence: 95%